PERANCANGAN PENGALAMAN PENGGUNA APLIKASI PENDATAAN TOOLS PERANGKAT LUNAK YANG DIGUNAKAN DALAM PERKULIAHAN DI FAKULTAS ILMU KOMPUTER UNIVERSITAS BRAWIJAYA DENGAN METODE DESIGN THINKING - Zeta Zidanne Bihesa; Agi Putra Kharisma; Dwija Wisnu Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Application to lectures is a major aspect that is undertaken while studying. Currently, there are still many lectures that do not provide clear details on what applications are used and where to download them in these courses, especially at FILKOM Universitas Brawijaya. Approximately 90% of students still get information regarding applications used through friends and lecturers manually as well as time goes by. Based on that, the author plans to design a mobile-based application that will carry out an internal software data collection system for FILKOM courses using the Design thinking method. This Design Thinking method was carried out so that research focuses on user experience so that it is suitable for understanding the needs of FILKOM students. For validation, usability testing on 20 respondents obtained an effectiveness aspect value of 91.75%, then for the results of the efficiency aspect of 0.076 goals/second, and the results of the satisfaction aspect of 81,875 which entered grade b, excellent rating, and acceptable category. For testing the UEQ questionnaire with attractiveness results of 1.70 in the good category, results from the perspicuity aspect of 1.41 in the above average category, results from the efficiency aspect of 1.80 in the good category, results from the dependability aspect of 1.69 in the category good, the results from the stimulation aspect are 1.55 in the good category, and the results from the novelty aspect are 0.95 in the above average category. Researchers also collect criticism and suggestions to improve the results of the solution design for the better.